Communication ethics in informational aggression conditions - Kochyna, Valentyna (Київський інститут Національної гвардії України, 2025)
In conditions of informational aggression, communication ethics is particularly important in the modern world where information is rapidly disseminated and can be used as a weapon. Professionalism and compliance with ethical standards play a key role in maintaining healthy communication. It is important to remember that any form of aggression can have negative consequences not only for individuals but also for organisations as a whole. Therefore, it is necessary to develop strategies to help maintain ethical standards in difficult situations
Keywords: Тези; communication ethics; informational aggression